In Quest of Tolstoy - McLean, Hugh (Studies in Russian and Slavic Literatures, Cultures, and History, 2008)
Lev Tolstoy has held the attention of mankind for well over a century. A supremely talented artist, whose novels and short stories continue to entrance readers all over the world, he was at the same time a fearless moral philosopher who explored and challenged the fundamental bases of human society-political, economic, legal, and cultural. Hugh McLean, Professor Emeritus of Russian literature at the University of California, Berkeley, has been studying and writing about Tolstoy for many years. In these essays he investigates some of the numerous puzzles and paradoxes in the Tolstoyan heritage, engaging both with Tolstoy the artist, author of those incomparable novels, and Tolstoy the thinker, who, from his impregnable outpost at Yasnaya Polyana, questioned the received ideas and beliefs of the whole civilized world. In two concluding essays, "Tolstoy beyond Tolstoy," McLean deals with the impact of Tolstoy on such diverse figures as Ernest Hemingway and Isaiah Berlin.